Paclitaxel and Gemcitabine Combinational Drug-loaded Mucoadhesive Delivery System in the Treatment of Colon Cancers - Guo, X.-Y.; Wang, P.; Du, Q.-G.; Han, S.; Zhu, S.-M.; Lv, Y.-F.; Liu, G.-S.; Hao, Z.-M. (Drug Research, 2015)
The combination of two different types of chemotherapeutic drugs via nanocarriers is emerged as a promising strategy for treating multiple cancers. Such a co-delivery system will synchronize the drug exposure and synergize the therapeutic effects. Herein, we prepared a paclitaxel (PTX) and gemcitabine (GEM)-loaded N-succinyl chitosan nanoparticles (NSC NP) to target colon cancer. NSC NP showed a pH sensitive swelling at colonic pH and exhibited a sequential release pattern for both the drugs. Binary drug combination exhibited a synergistic cytotoxicity against HT-29 colon cancer cells with a remarkable G2/M phase arrest. Specifically, in vivo antitumor efficacy study showed that NSC NP prolonged the survival time of tumor-bearing mice up to 45 days wherein 50% of mice were still alive. Therefore, these results suggest that co-delivery of drugs with a suitable delivery system could potentially improve the therapeutic efficacy in colon cancers. The study can be further continued by using different types of chemotherapeutic drugs that targets different molecular targets using pH-sensitive nanocarriers.
Keywords: combinational drug; pH sensitivity; nanoparticles; colon cancer; chemotherapeutic efficacy